2018
DOI: 10.2478/ethemes-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Team Learning Processes and Activities in Organization: A Case Study

Abstract: Organizations in today's environment are relied on teams and their learning as key determinants for survival and success. The aim of this paper is to identify the key team learning processes and activities in organizations and to examine how the eventual appearance and growth of the problems in team impact on those processes and activities. Research was conducted in nine teams with 79 members in one public service organization located in Belgrade, Serbia, using interview and questionnaire techniques. Descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Since the motivation of employees to work is increasingly moving from material aspect to immaterial, managers try to "enrich" work of employees through: creativity, innovation, greater autonomy in work, flexibility of working hours, teamwork (Aleksić-Glišović, Jerotijević & Jerotijević, 2019), confidencerelied communication, readiness to listen and understand, empathy and respect, rewarding even a small success, tolerance of small mistakes, career possibilities (Bećirović, et al 2020. ), as well as avoid vaguely defined roles of team members, lack of trust between them, inadequate reward system (Lazarević & Lukić, 2018).…”
Section: Nature Of Employees' Motivationmentioning
confidence: 99%
“…Since the motivation of employees to work is increasingly moving from material aspect to immaterial, managers try to "enrich" work of employees through: creativity, innovation, greater autonomy in work, flexibility of working hours, teamwork (Aleksić-Glišović, Jerotijević & Jerotijević, 2019), confidencerelied communication, readiness to listen and understand, empathy and respect, rewarding even a small success, tolerance of small mistakes, career possibilities (Bećirović, et al 2020. ), as well as avoid vaguely defined roles of team members, lack of trust between them, inadequate reward system (Lazarević & Lukić, 2018).…”
Section: Nature Of Employees' Motivationmentioning
confidence: 99%
“…Development of enthusiasm among employees who focus their efforts on achieving goals of the organization leads to better results (Vorina, Simonič & Vlasova, 2017). Paying attention to employees can increase their productivity, increase level of job satisfaction and meeting needs through rewards for achievement, because it is in human nature to expect a reward for performing a certain activity (Vroom, 1964), while avoiding vaguely defined roles of team members, lack of trust between them, and inadequate reward system (Lazarević & Lukić, 2018).…”
Section: Employee Satisfaction As a Determinant Of Motivationmentioning
confidence: 99%
“…Some researchers have proposed that organizational structures respond to the diverse individual needs of businesses (Conner and Douglas, 2005). The other concluded that the organizational structure that has worked in business practice is characterized by a more flattened structure, decentralized decision making, more cooperation and coordination, knowledge sharing among employees, teamwork, horizontal communication, flexibility (Bryant, 2014;Lazarević and Lukić, 2015;Lee and Edmondson, 2017;Lazarević and Lukić 2018).…”
Section: Literature Reviewmentioning
confidence: 99%